Nudging Demand for Academic Support Services: Experimental and Structural Evidence from Higher Education - Todd Pugatch; Nicholas Wilson (Institute of Labor Economics (IZA), 2020)
More than two of every five students who enroll in college fail to graduate within six years. Prior research has identified ineffective study habits as a major barrier to success. We conducted a randomized controlled advertising experiment designed to increase demand for academic support services among more than 2,100 students at a large U.S. public university. Our results reveal several striking findings. First, the intervention shifted proxies of student attention, such as opening emails and self-reported awareness of service availability. However, the experimental variation indicates that approximately one-third of students are never attentive to student services. Second, advertising increased the use of extra practice problems, but did not affect take-up of tutoring and coaching, the other two services. Structural estimates suggest that transaction costs well in excess of plausible opportunity costs explain the differences in service use. Third, the characteristics of advertising messages matter. Several common nudging techniques—such as text messages, lottery-based economic incentives, and repeated messages—either had no effect or in some cases reduced the effectiveness of messaging.
Keywords: A22; D91; I23; M31; 330; email; higher education; incentives; nudges; text; randomized control trial